2022
DOI: 10.1371/journal.pone.0264185
|View full text |Cite
|
Sign up to set email alerts
|

Links between types of value orientations and consumer behaviours. An empirical study

Abstract: The present study concerns the phenomenon of the co-dependence of value orientations and consumer behaviours. Although the idea of the overall connections between both areas is not new, the article contributes to the knowledge about relations between very specific consumer behaviours and social value orientations among people married or in an informal partnership. Using the obtained data, we examine to what extent the prosocial, reciprocal, and egoistic value orientations coexist with compensative, compulsive,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In the previous literature, a close relationship between neuroticism and low self-esteem has been reported [49] and, also from a clinical perspective, psychological distress is linked to weak self-worth [81,82]. As for the influence of self-esteem on CB observed in the model, it should be mentioned that different empirical studies have reported that a negative self-worth contributes to predicting CB [15,36,65]. In this regard, there are a number of different hypotheses that can be found in the literature with regard to the function and/or usefulness, for some people, of CB: improving identity [83], a way to manage or enhance a poor sense of self [84] and bolstering one's self-esteem [85].…”
Section: Explaining the Direct And Indirect Effects Of Neuroticism In...mentioning
confidence: 86%
See 1 more Smart Citation
“…In the previous literature, a close relationship between neuroticism and low self-esteem has been reported [49] and, also from a clinical perspective, psychological distress is linked to weak self-worth [81,82]. As for the influence of self-esteem on CB observed in the model, it should be mentioned that different empirical studies have reported that a negative self-worth contributes to predicting CB [15,36,65]. In this regard, there are a number of different hypotheses that can be found in the literature with regard to the function and/or usefulness, for some people, of CB: improving identity [83], a way to manage or enhance a poor sense of self [84] and bolstering one's self-esteem [85].…”
Section: Explaining the Direct And Indirect Effects Of Neuroticism In...mentioning
confidence: 86%
“…Similarly, it has been documented that compulsive buyers as compared to buyers who do not present with this problem, score significantly lower in self-esteem [17,[62][63][64]. Furthermore, low self-esteem has proved to be a significant predictor of CB [14,15,36,65].…”
Section: Introductionmentioning
confidence: 94%
“…Specifically, and on the basis of the classification of values made in the personal values theory [ 78 ], the positive association of stimulation and hedonism with compulsive buying has been confirmed [ 79 , 80 ], as well as the protective effect of self-transcendence and conservation values in the development of compulsive buying [ 79 ]. Research has shown that people who are characterized by a reciprocal and egoistic value orientation show high vulnerability to compulsive buying, while prosocial value orientation acts as a protective factor for this behavior [ 81 ].…”
Section: Level Ii—personal Concerns Characteristic Adaptations and Co...mentioning
confidence: 99%
“…(4) Egoistic-altruistic orientations. Egoistic or individualist value orientation is related to the preference and maximization of own benefits and outcomes of the work with indifference to the outcomes for other people, society and environment (Adamczyk et al, 2022). This orientation has a lot of parallels with the instrumental orientation in respect to work values.…”
Section: Introductionmentioning
confidence: 99%